Correlation of REG1A, Claudin 7 and Ki67 expressions with tumor recurrence and prognostic factors in superficial urothelial urinary bladder carcinomas - Elif Yamuç; Nagehan Özdemir Barışık; Sibel Şensu; Fatih Tarhan; Cem Cahit Barışık (Wolters Kluwer Medknow Publications, 2022)
Aım: Superficial urothelial urinary bladder tumors are neoplasms that frequently recur and have a potential for invasion and metastasis. REG gene family is composed of various acute phase reactants, lectins, antiapoptotic factors, and growth factors that are effective on pancreatic island cells, neural cells, and epithelial cells. REG1A and REG1B are two forms of the human REG1 gene. It is reported that they are expressed in several cancers and are correlated with the prognosis of the patient. Claudins are integral transmembrane proteins that interconnect cells. However, their role in human tumorigenesis is extremely controversial. The aim of this study is to evaluate the relationship of REG1A, claudin 7 protein expressions, and Ki67 proliferation index in superficial urothelial urinary bladder tumors with well-known parameters of prognosis and tumor recurrence, and also to clarify whether these parameters are independent prognostic factors or not. Materials and Methods: A hundred and eleven patients diagnosed with superficial urothelial carcinoma between 2011 and 2016 years in our hospital and followed up in our urology clinic were included in this study. The slides prepared from paraffin blocks were immunohistochemically stained with REG1A, claudin 7, and Ki67 antibodies. Results: REG1A showed positive staining in 37 (33%) and negative staining in 74 (67%) of urothelial tumors. Claudin 7 was positive in 24 (22%) and negative in 87 (78%) cases. REG1A expression showed a positive correlation with tumor stage and tumor recurrence; a high Ki67 proliferation index was positively correlated with tumor stage and grade. The loss of claudin 7 expression was related to tumor recurrence. Besides, tumors with REG1A expression and claudin 7 loss had a shorter survival independent of recurrence. Conclusıon: In urothelial tumors, REG1A expression and loss of claudin 7 might be significant markers of prognosis that predict tumor recurrence.